Current balancing of cascaded H-bridge converters for PV systems with partial shading. Issue 6 (2nd November 2015) - Iannuzzi, Diego; Pagano, Mario; Piegari, Luigi; Tricoli, Pietro
Abstract : Purpose: – The purpose of this paper is to propose a new converter topology for integrating PV plants constituted by many panels into the grid. The converter is capable of implementing MPPT algorithms on different subset of modules and can balance the different energy supplied by panels differently irradiated. The output voltage presents a very low ripple also if small filters are used for grid connection. Design/methodology/approach: – In the paper, at first the converter configuration is presented. Then a control strategy for obtaining, at the same time the distributed MPPT and the power balancing on the three phases is proposed. Finally, by means of numerical simulations, the good performances of the proposed converter are shown. Findings: – The proposed converter, lent from MMC configurations, is deeply studied and a suitable control strategy is well analyzed in the paper. Analytical model for voltage and current balancing are given. Research limitations/implications: – The analysis presented in the paper complete some studies started in the last years and partially presented in previous scientific papers. It reaches a final point and gives all the specific for the realization of the converter and of its control. Practical implications: – The paper gives all the instrument to design and realize a PV power plant integrated into building façade. Originality/value: – The converter and the control for voltage and current balancing presented in this paper represent a significant original contribution of this work.